2009
DOI: 10.1002/14651858.cd001506.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Nebulised hypertonic saline for cystic fibrosis

Abstract: BackgroundLung disease in cystic fibrosis is characterised by impaired mucociliary clearance. Hypertonic saline has been shown to enhance mucociliary clearance in vitro and this may act to lessen the destructive inflammatory process in the airways. ObjectivesTo investigate the effects of treatment with nebulised hypertonic saline on people with cystic fibrosis compared to placebo and or other treatments that enhance mucociliary clearance. Search methods'We searched the Cochrane Cystic Fibrosis and Genetic Diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(42 citation statements)
references
References 22 publications
0
39
0
3
Order By: Relevance
“…13 However, further not-yet-elucidated mechanisms other than tonicity may underlie the clinical benefits observed in patients. In vivo and in vitro studies performed by our group suggested that some of the beneficial anti-inflammatory effects mediated by HTS could be due to hyperosmolarity rather than hypertonicity.…”
Section: Introductionmentioning
confidence: 99%
“…13 However, further not-yet-elucidated mechanisms other than tonicity may underlie the clinical benefits observed in patients. In vivo and in vitro studies performed by our group suggested that some of the beneficial anti-inflammatory effects mediated by HTS could be due to hyperosmolarity rather than hypertonicity.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Nebulized hypertonic saline has been shown to improve mucociliary clearance and sputum expectoration in patients with cystic fibrosis and with mucociliary dysfunction. [15][16][17] It is hypothesized that hypertonic saline may be useful in bronchiolitis by absorbing water from the submucosa, thereby decreasing edema and improving mucociliary function. To date, there have been 4 trials investigating the use of nebulized 3% hypertonic saline solution in infants with viral bronchiolitis.…”
mentioning
confidence: 99%
“…В исследовании S.Donaldson et al показано, что до стоверное повышение мукоцилиарного клиренса продолжается как минимум в течение 8 ч после ин галяции 7% го раствора [32]. Разработанные схемы ингаляций ГРХН обязательно включают сочетанное назначение бронхолитических препаратов коротко го действия, препятствующих развитию бронхоспаз ма [2,10,[32][33][34].…”
Section: гипертонический раствор хлорида натрияunclassified